Job Contact Networks and Wages of Rural-Urban Migrants in China - Wenjin Long; Simon Appleton; Lina Song (Institute for the Study of Labor (IZA), 2013)
In nationally representative household data from the 2008 wave of the Rural to Urban Migration in China survey, nearly two thirds of rural-urban migrants found their employment through family members, relatives, friends or acquaintances. This paper investigates why the use of social network to find jobs is so prevalent among rural-urban migrants in China, and whether migrants face a wage penalty as a result of adopting this job search method. We find evidence of positive selection effects of the use of networks on wages. Users of networks tend to be older, to have migrated longer ago and to be less educated. In addition, married workers and those from villages with more out-migrant are more likely to use networks, while those without local residential registration status are less likely. Controlling for selectivity, we find a large negative impact of network use on wages. Using job contacts brings open access to urban employment, but at the cost of markedly lower wages.
Keywords: J24; J31; O15; 330; social network; job contact; wage; rural-urban migrants; switching regression; China